Exploring the American Family Values in “Yes Day” Movie (A Cinematic Analysis): American Family Values (A Cinematic Analysis) - Nirwana (Journal of Islamic Culture and Literature (JICeL), 2023)
This study intends to investigate how American family values are portrayed and represented in the film "Yes Day." The study explores the themes, characters, and narrative components of the movie using a cinematic analysis approach to discover the underlying values and messages related to the American family. An overview of "Yes Day" as a cultural phenomenon in American society is given at the outset of the study. It focuses on the practice’s potential effects on family dynamics and values while examining the practice’s history and significance. The analysis next turns its attention to the actual film, going over its story, characters, and general presentation. The results of this study help us understand how American family values are portrayed in modern movies. The study also emphasizes some values such as togetherness, stability, and loyalty. Overall, this study provides a thorough examination of how the American family values depicted in "Yes Day" were captured through cinematic analysis. It contributes to the current conversation about family values in American culture and offers insights into the intricacies of modern family interactions. Keywords: American Family Values, Cinematic Analysis, Yes Day Movie